PENGARUH MUTASI DAN PROMOSI JABATAN TERHADAP KINERJA PEGAWAI DI PUSAT PELATIHAN MANAJEMEN DAN KEPEMIMPINAN PERTANIAN (PPMKP) CIAWI - BOGOR - Suyati, Suyati; Yuningsih, Erni (Fakultas Ekonomi Universitas Djuanda, 2016)
This study aims to determine: 1) the perception of employees against transfer and promotion 2) simultaneously and partially the effect of mutations and promotions on employee performance. The research method used descriptive and verification method. Test instrument data using product moment to test the validity and reliability with Cronbach alpha. Methods of data analysis used multiple regression analysis, correlation analysis and analysis of determination and hypothesis test F-test and t test. The results showed that the variables of personnel transfers and promotions of powerful positions simultaneously (together) on employee performance. Partially personnel transfers influence on employee performance and promotion effect on employee performance.Keywords: Mutation, Promotion, Performance